Mortality and Walking Ability Impairment in Patients with Fragility Fractures of the Proximal Femur - Prado Costa, Rui; Serviço de Medicina Física e de Reabilitação do Centro Hospitalar São João, Porto, Portugal (2021)
Introduction: Fragility fractures of the proximal femur (FFPF) are associated with increased mortality and functional impairment. The main aim of this work was the determination of factors associated with walking ability impairment six months post-fracture and one-year mortality.Methods: Retrospective cohort study comprising all patients admitted to a hospital center. Data were collected from electronic medical records. A comparative analysis was performed for several factors regarding walking ability impairment by six month post-fracture and one-year mortality post-fracture.Results: Five hundred twenty two patients were admitted with FFPF. Around 49% had walking ability impairment by six month post-fracture compared to pre-fracture status. Analyzing the subgroup of patients that had been integrated in rehabilitation programs on National Network of Integrated Continued Care (RNCCI), only 11% of patients recover the pre-fracture level of walking capacity during Orthopedics inpatient stay with additional recover in 28% of patients through rehabilitation intervention in RNCCI. No significative associations were found between walking ability impairment by six month and the analyzed variables. Died within oneyear post-fracture, 18% of the patients. Previous inability to walk (p=0.094), inability to walk by six month postfracture (p=0.024), femoral neck fractures (p=0.006) and surgery with arthroplasty and hemiarthroplasty (p=0.047 and p=0.033 respectively) had significant inferior survival curves. The calculated logistic regression model showed that male gender (OR 2.95; p=0.033) and walking ability impairment by six month post-fracture (OR 7.43; p=0.024) were predictors of one-year mortality.Conclusion: One-year mortality and walking ability impairment are considerable in patients with FFPF. Early comprehensive rehabilitation should be prioritized on those patients as it can impact their vital and functional prognosis.